Chapter 11 - Traditional uses, processing, and markets: the case of sweetpotato (Ipomoea batatas (L.) Lam.) - Heider, B.; Paredes, N.J.; Sørensen, M. (2024)
As an ancient Latin American and major root crop, the sweetpotato has a long domestication history involving large areas in Central and South America. The sweetpotato forms an important ingredient in numerous traditional diets. Processing enables the usability of sweetpotato in various forms for longer durations. All the plant parts, roots, vines, and young leaves are used as foods, animal feeds, and traditional medicine worldwide. Postharvest processing of sweetpotato involves grading and sorting, cleaning, peeling, drying or secondary processing, and storage. Most of the dry matter in the sweetpotato consists of carbohydrates, primarily starch and sugars. Residues from sweetpotato starch and juice processing of commercial varieties are useful sources of dietary fiber. Among the novel processed uses are purée, juice, and canned, frozen, dried, and snack products. Commercial utility of sweetpotato is comprised of conventional and composite ingredient-based foods, starch, and industrial products.